A sociolinguistic analysis of tourism in Brazilian travel blogs about the tourist destination Mount Roraima - Cavalcante, Jordana de Souza; Lacerda, Paulo Henrique Ferreira; Perinotto, André Riani Costa (Anais Brasileiros de Estudos Turísticos, 2025)
This article presents a multimodal study that analyzes five blog posts about Mount Roraima, written by Brazilian travel bloggers. The objective is to understand how the sociolinguistic approach to tourism uses blogs as sources of linguistic and semiotic materials for the social construction of categories such as "tourist destination." Based on Halliday’s Systemic Functional Linguistics, the study develops an analytical structure of text and static images to represent Mount Roraima and highlight sociolinguistic characteristics of the blogs. The analysis reveals that Mount Roraima is portrayed as a destination of identity, emphasizing authentic and unique experiences through texts and images. The posts highlight authenticity and uniqueness, with adjectives that encode values of appreciation and interactive qualities, suggesting how Mount Roraima is perceived and presented. The conclusions have important implications for sociolinguistic theory and tourism marketing practices.